Analisis Pemikiran Syeikh Wan Ahmad Bin Muhammad Zain Al-Fatani Dalam Konsep Ilahiyyat - Md Hilmy, Sulaiman (2012)
This qualitative study aims to analyse the thought of Syeikh Ahmad bin Wan Muhammad Zain al-Fatani (hereinafter referred to al-Fatani) associated with the concept of ilahiyyat through his Tawhid works. The specific objective of this study, firstly, is to explain the calibre of a Malay scholar and his contribution to the development of Tawhid knowledge. Secondly, is to clarify the thought of al-Fatani relating to the concept of ilahiyyat, and the thirdly, is to analyse the position of al-Fatani’s thought on some ilahiyyat issues. This study used the library research method in which al-Fatani’s views and approaches in knowledge of Tawhid were evaluated and compared with the other views of honoured scholars. The methods used in this study are the inductive and deductive analysis, and comparative analysis. The study found that the thought of al-Fatani in ilahiyyat concept was fully in accordance with the understanding and approach of Asyacirah doctrine and he did not accept any other thoughts except Asyacirah doctrine and the understanding of the majority of Ahlu Sunnah wa al-Jamacah’s scholars. Due to that, al-Fatani did not highlight any new thought and approach which would be significant in explaining the ilahiyyat concept. His thought tended to explain the understanding of ilahiyyat concept based on the approach of previous Asyacirah scholars such as al-Baijuri. This study will add value to the strengthening of faith and spreading the knowledge of Tawhid which have been deep-rooted with the Muslims throughout the Archipelago, particularly in Malaysia.